FABRICATION AND ASSESSMENT OF LERCANIDIPINE HYDROCHLORIDE SOLID DISPERSIONS FOR SOLUBILITY PREFERMENT USING POLYMER COMBINATION - REDDY, NAZEMOON; DUGASANI, SWARNALATHA; NAYAKANTI, DEVANNA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: An attempt has made in fabricating solid dispersions (SDs) by taking lercanidipine hydrochloride (LCD) as a model drug. Methods: The SDs were made using a poly mix of poly vinyl pyrrolidone (PVP) K-30, Poloxamer-188, and hydroxy propyl methyl cellulose (HPMC) K4M. Different proportions of LCD: polymer mix in 1:1, 1:3, 1:5, and 1:7 ratios were fabricated as SDs by solvent evaporation and melting method, further compressed into tablets. The LCD SDs were assessed for physicochemical, and LCD release possessions. Results: The results were observed to be attractive with the increase in solubility LCD SD (F-3 and F-7) with 1:5 ratios of LCD. Conclusion: The study concludes that the poly mix of PVP K-30, Poloxamer-188, and HPMC K4M and was found to be a better combination for elevating the solubility and release of LCD from the SDs.